Implementasi Sistem Informasi Pengukuran Kinerja Karyawan di PT Hetra Vexa Group dengan Pendekatan Key Performance Indikator - Akmal Yaqien; Veri Arinal (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
Employee performance is a crucial factor in determining the success of an organization. PT Hetra Vexa Group, a company engaged in software application sales, previously relied on a manual and subjective performance appraisal system. This condition created several problems, such as lack of objectivity, difficulties in real-time performance monitoring, and delays in strategic decision-making. To address these issues, this study implemented a mobile-based employee performance measurement system using the Key Performance Indicator (KPI) approach combined with the Objective and Key Results (OKR) method. The system was developed using the Waterfall model, which consists of requirement analysis, design, implementation, and testing stages, while system evaluation was conducted through Black Box Testing. The system features employee data management, KPI indicators, automated appraisal, and a monitoring dashboard displaying real-time evaluation results. KPI was applied to determine indicator weights, whereas OKR was used to map organizational strategic objectives into individual targets. The testing results show that the system produces more objective, accurate, and standardized performance appraisals. Employees with a KPI score ≥ 80% are categorized as high achievers and eligible for rewards, while those with a score ≤ 60% are categorized as low performers and subject to punishment. The system implementation has proven to increase appraisal efficiency by 40% compared to the previous manual method and significantly reduce subjectivity in managerial assessments. The average efficiency improvement was recorded at 80.63%, reflected in the reduction of performance evaluation time from eight days to one working day, a decrease of document costs by 80%, a reduction of data errors by 80%, and acceleration of performance report access from twenty working days to five working days. Therefore, this system contributes to enhancing productivity, work motivation, and sustainable achievement of organizational goals.